Exploring Google Bard's (Gemini) Role in Enhancing Research Articles in Computational Thinking and Mathematics Education - supriyadi, edi (Papanda Publisher, 2024)
This research aims to explore the role of Google Bard (Gemini) in facilitating the creation of research articles in computational thinking and mathematics education. The study provides a nuanced understanding of the capabilities and potential contributions of Google Bard in academic research within these domains. Employing Google Bard as the primary method, the researcher conducted a systematic search in the Scopus database, focusing on articles related to computational thinking and mathematics education published within the last three years by authors from Indonesia. The search resulted in four articles, with three accessible for download. The researcher renamed and stored these articles in a designated Google Drive folder, emphasizing the integration of Google Bard in information retrieval and organization. The findings highlight Google Bard's systematic utility, demonstrating its role in efficient document organization, retrieval, and creation of research articles. The tool's versatility is evident in its application across diverse studies, contributing to the advancement of cognitive skills and alignment with contemporary educational frameworks. Noteworthy features, including multiple drafts and audio responses, enhance user experience and accessibility. Scholars and educators are encouraged to delve deeper into Google Bard's features for collaborative efforts, efficient document organization, and information retrieval, thereby contributing to a more dynamic and efficient research process in the fields of computational thinking and mathematics education. Continuous exploration and adaptation of Google Bard's capabilities hold the potential to unlock its full functionality and further enrich scholarly pursuits in these domains.